2015
DOI: 10.1515/pjs-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life of women treated due to breast cancer using amputation or breast conserving surgery in the early postoperative period

Abstract: With respect to Global Health Status/QoL and Physical Functioning, the quality of life of women in the early postoperative period was similar in women after breast amputation and those who underwent breast conserving surgery. Patients treated with breast conserving surgery had a better score for body image, while those who underwent amputation more often suffered from arm symptoms, such as pain, oedema, and problems with raising of the limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 5 publications
2
18
0
1
Order By: Relevance
“…In our study, effects of the early rehabilitation program three months after surgery point to an increase in average summation scores in all domains and components in both patient groups. These results are also supported by studies done in Denmark, Poland, and Spain [2,17,19,20,25].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our study, effects of the early rehabilitation program three months after surgery point to an increase in average summation scores in all domains and components in both patient groups. These results are also supported by studies done in Denmark, Poland, and Spain [2,17,19,20,25].…”
Section: Discussionsupporting
confidence: 74%
“…A heterogeneous rehabilitation approach with specific rehabilitation interventions and different methodological approaches are described in numerous studies [5-10, 12, 13]. Most authors reported their positive influence on the QoL of those suffering from and being treated for breast cancer [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, many patients admit that the support of family and friends motivates them to cope with the disease [7]. In another study, 3 months after being operated on, women assessed their general health condition as moderate, and it was worsened mainly by tiredness and dyspnea [8]. In a different study, a similar group of patients in the same period after mastectomy assessed their life quality as poor.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was found to have equivalent outcomes, both in terms of overall disease‐free survival and lifestyle scores, when compared with mastectomy . Data from several studies has shown the advantage of BCT over mastectomy with regard to patient QoL; however, little is known about QoL of patients undergoing OBCS.…”
Section: Introductionmentioning
confidence: 99%